Assessment Of Awareness Level and Perception In Usage Of Plastic Bags And Its Hazards Among Secondary School Students - Din, Mohi Ud; Arif, Zain; Naveed, Hafiz Usama; Tauseef, Maryam; Yaseen, Nouman; Mahboob, Talha (Journal of Rawalpindi Medical College, 2024)
Objective: The objectives of the study were to determine the frequency of plastic bag usage among secondary school students of Islamabad and to assess their knowledge about plastic bag-associated pollution, its disposal and legislation. Methods: A cross-sectional descriptive study was conducted from December 2020 to December 2021 in high schools in Islamabad. A sample size of 377 was calculated through Raosoftware comprising 53.6% male and 46.4% female students. Ethical approval was taken with the number ERC/ID/47. A consecutive non-probability sampling technique was used. Inclusion criteria were students of the 8th to 10th class and those who gave consent and filled out the questionnaire. A properly structured questionnaire was used. SPSS version 25 was used for data analysis. Frequencies and percentages were calculated. A chi-square test of significance was applied for categorical variables. A p-value less than 0.05 was considered statistically significant. Results: About 97.6 % of the participants considered plastic as a contributory factor to environmental pollution and 67.6% used plastic bags as carrying materials. Awareness about alternatives like clothed bags was observed in about 85.9% of students. Regarding legislation, half of the study population opined that the community is responsible for banning plastic bags while the other half suggested that it’s the responsibility of the Government. Significant p-value was observed between gender (0.036), age (0.000), education (0.000), knowledge about plastic hazards (0.01), health hazards (0.029) and usage of plastic bags. Conclusion: The usage of plastic bags was high among the students. Although they were well aware of the hazardous effects of plastic bags, most of them were routinely using plastic bags for daily activities. Different factors that were responsible for the higher usage of plastic bags included a lack of alternatives to plastic bags, easy availability, low cost and lightweight. Keywords: Awareness, plastic bags, legislation, hazards.